Welfare Gains from Optimal Policy in a Partially Dollarized Economy - Carlos Gustavo Machicado (Institute for Advanced Development Studies (INESAD), 2006)
This paper evaluates welfare under optimal monetary and fiscal policy in a dynamic stochastic model of currency substitution and capital. It shows that in a partially dollarized economy, the main optimal policy results, i.e. the Friedman Rule and the zero capital tax, hold. Welfare implications of these optimal policies are computed for the Bolivian economy using a second-order approximation technique. The primary conclusions are that the welfare gains under optimal monetary policy are negligible. The welfare gains when optimal fiscal policy is considered alone or in conjunction with optimal monetary policy are sizable and come from the increase in real variables and also by the increase in real balances in local currency. Thus, welfare gains are negatively related to dollarization.
Keywords: F31; E61; E63; 330; Dollarization; Optimal Fiscal and Monetary Policy; Second-order approximation technique.